Pre- and post-immigration factors associated with cigarette use among young adult recent Latinx immigrants during their initial year in the U.S. (2nd January 2022) - Sanchez, Mariana; Romano, Eduardo; Wang, Weize; Barton, Alexa; Ali, Bina; Villalba, Karina; Westick, Ashly
ABSTRACT: Background : Evidence indicates escalating rates of cigarette use among foreign-born Latinx as their time in the U.S increases. As such, it's important to understand shifts in pre- to post-immigration smoking patterns early in the immigration process and its associated factors. Objectives : To examine 1) cigarette use among recent Latinx immigrants (RLIs) during their initial year in the U.S.; 2) whether cigarette use after immigration is influenced by smoking patterns in immigrant's country of origin; and 3) associations between pre/post immigration sociocultural factors and changes in cigarette use after immigration. Methods : Baseline data were utilized from an on-going longitudinal study of 540 young adult (50% females) RLIs. Inclusion criteria was being between ages 18 and 34, residing in Miami-Dade County, Florida, and having immigrated from a Latin American country within the past year Results : Approximately 31% of participants reported being smokers in their country of origin while 26% were current smokers (while residing in the U.S). Post-immigration cigarette use was substantially influenced by country of origin cigarette use (V = .68); 84% of pre-immigration smokers reported no change in smoking frequency, while 11% lowered and 6% increased their cigarette use post-immigration. Reduction in smoking after immigration was more likely among participants with higher pre-immigration social support (aOR = 1.87) and less likely among those residing in high-crime neighborhoods (aOR = .84). Conclusion : Interventions aimed to discourage cigarette use should begin early in the immigration process and account for RLIs' pre-immigration smoking patterns. Interpersonal supports and neighborhood contextual factors should be considered when developing smoking cessation programs with this population.